A case study: using multiple-choice tests at university level courses – preparation and supporting infrastructure. (16th June 2010) - Cupic, M.
In this paper, we will present a case study of using multiple-choice tests for university level courses such as digital logic and artificial intelligence. It is a well known fact that multiple-choice questions can be used to assess student's knowledge – not only student's recall, but also the verification of student's analysis and synthesis abilities. We will give an example of questions for assessment of all three types. We will consider how computers can be used to prepare such tests and what is needed to automatically grade such tests. We will present an open source application that we developed to foster such a process.